2022
DOI: 10.33200/ijcer.829411
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Initiative Climate on the Relationship between Distributed Leadership and Organizational Resilience in Schools

Abstract: This article may be used for research, teaching, and private study purposes.Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…Thus, it can be argued that the views of the participants on OR were similar in all dimensions. This finding is supported by Limon, Dilekçi and Demirer (2021).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, it can be argued that the views of the participants on OR were similar in all dimensions. This finding is supported by Limon, Dilekçi and Demirer (2021).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 67%
“…In addition, Gültekin (2019) found that there was a moderate and negative relationship between organizational blindness and OR. Limon, Dilekçi, & Demirer (2021) found a positive and significant relationship between distributed leadership and OR. It was also found in the present study that there was a significant relationship between SE and all dimensions of ORS.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 88%
See 2 more Smart Citations
“…On taking up their new role, principals are at the eye of the storm of personal and organizational change that characterizes this stage (Limon et al, 2021). These change processes naturally entail significant emotional and mental challenges (Slater, Garcia, & Mentz, 2018).…”
Section: The Complexity Of Entering Principalshipmentioning
confidence: 99%